AOX removal from pulp and paper wastewater by Fenton and photo-Fenton processes: a real case-study - Ribeiro, João Peres (2020)
D0 bleaching wastewater from E. globulus Kraft pulping industry was treated by Fenton and photo-Fenton processes. The aim was to optimise the operational conditions for adsorbable organic halides (AOX) removal, namely oxidant concentration, [H2O2], catalyst concentration, [Fe2+], and treatment time, using the central composite experimental design (CCED) tool. Temperature and pH were set at 60 ºC and 2, respectively, which are similar to the natural values of the D0 bleaching wastewater. Both processes showed potential to remove AOX from D0 with 177 - 178 mM H2O2 and 10 min reaction time. Maximum AOX removal was 85 % for the Fenton process with 8.5 mM Fe2+, and 95 % for the photo-Fenton process with 2.0 mM Fe2+ and UV irradiance 142 W.m- 2. For both methods, the only statistically significant variable (p=0.05) was the concentration of oxidant, [H2O2].